Soil aluminum oxides determine biological nitrogen fixation and diazotrophic communities across major types of paddy soils in China - Wang, Xiaojie; Liu, Benjuan; Ma, Jing; Zhang, Yanhui; Hu, Tianlong; Zhang, Heng; Feng, Yucheng; Pan, Hongli; Xu, Zhenwen; Liu, Gang; Lin, Xingwu; Zhu, Jianguo; et al. (Soil biology & biochemistry, 2019)
Biological nitrogen fixation (BNF) contributed greatly in maintaining the fertility of paddy soils without the application of chemical fertilizers for thousands of years. However, factors affecting the BNF and composition of diazotrophs in paddy soils across large geographic scales are still largely unknown. In this study, the field-based 15N2 labeling technique and nifH gene high-throughput sequencing were applied to four types of paddy soils collected from northeast to southwest China, representing major rice-growing areas. Results showed that the BNF amount had distinct geographical patterns and ranged from 2.2 ± 0.5 to 20.1 ± 3.7 kg N ha−1 during 42 days 15N2 labeling period, which was positively correlated with the abundance of Nostocales species. Among the soil properties analyzed, the contents of amorphous aluminum oxides may play a key role in determining the BNF amount and major N2-fixers across all paddy soils using a random forest model. Overall, our study demonstrates the potential biotoxic effects of aluminum oxides on the BNF in paddy soils in southern China and may has important implications for the enhancement of BNF in acidic Ultisols and Oxisols. •Biological nitrogen fixation (BNF) of paddy soils had distinct geographical patterns across Northeast to Southwest of China.•BNF amount was positively correlated with the abundance of some Nostocales species.•Soil amorphous aluminum oxide was found to be key factor affecting the BNF and diazotrophic communities.